Regards d’enseignants québécois sur les élèves doués : points de vue diversifiés - Lagacé-Leblanc, Jeanne; Courtinat-Camps, Amélie; Massé, Line; Capdevielle, Valérie; Baudry, Claire; Bégin, Jean-Yves; Couture, Caroline; Verret, Claudia; Nadeau, Marie-France (Canadian Journal of Education/Revue canadienne de l’éducation, 2020)
This study examines teachers’ perceptions of gifted students in their class, in a Quebec school service centre, and the influence of personal and contextual variables. The sample consists of 21 primary school teachers (18 women and 3 men). After the lexical analysis carried out with the Alceste software, four specific classes of statements emerge from the teachers’ discourse. In addition, age, teaching cycle, type of class, number of years of experience, involvement in an intervention plan and experience with giftedness predict the heterogeneity of the perceptions of teachers towards giftedness. The results suggest more traditional and stereotypical perceptions of giftedness by teachers. Keywords: perceptions, representations, teachers, giftedness, characteristics, high potential, lexical analysis